Effects of belief generation on social exploration, culturally-appropriate actions, and cross-cultural concept learning in a game-based social simulation. (October 2020) - Gjicali, Kalina; Finn, Bridgid M.; Hebert, Delano
Abstract: This study primarily examined whether belief generation had effects on indicators of cross-cultural competence measured within a game-based social simulation. Participants (N = 433) played a game simulating an artificial culture with norms embodying two cultural concepts: hierarchy and collectivism. Participants were randomized into one of three conditions and completed three game quests: (1) Beliefs All (entered their beliefs about the culture after each quest), (2) Beliefs at End (entered their beliefs at the end of the game), or (3) No Beliefs (never entered their beliefs). We evaluated the degree to which metacognitive reflection, elicited through the frequency of belief generation, had effects on social exploration, the proportion of culturally-appropriate actions, and players' conceptual knowledge of the cultural system at the end of the game. Results indicated that the Beliefs All condition outperformed at least one of the alternative experimental conditions on each of these outcomes, each of which represented an important indicator of cross-cultural competence as measured through game performance metrics. A secondary goal of this work was to examine the degree to which within-game process data predicted game performance, irrespective of belief generation. Social exploration indicators predicted game performance, signifying that taking conversational turns and making attempts to build positive rapport with game characters led to a better understanding of the values upheld in the simulated culture. Subsequent cluster analyses resulted in four different types of learner clusters (fast, slow, none, and inconsistent learning gains) which emerged through game actions. Results indicated that learner clusters and belief generation condition had independent associations with cross-cultural concept learning, suggesting that there are individual differences that explain cross-cultural competence as measured within the context of a game-based assessment. Implications of this research are expansive and include: (1) recommendations for the development of social simulation games for cultural training, (2) the pedagogical uses of educational games to promote students' knowledge of cross-cultural concepts, and (3) the use of belief generation as a mechanism for promoting cross-cultural concept learning in interventions and for professional development purposes. Highlights: This study investigates people's cross-cultural competence within a game-based environment. The game is a social simulation of an artificial culture with specific cultural norms. The mission of the game is to interact in "culturally appropriate ways" in order to complete the quests. Experimental effects suggest that cognitive reflection facilitates cross-cultural concept learning. There are individual differences in cross-cultural competence, irrespective of belief generation.